The development of creative industries in Malaysia as experienced by Les’Copaque Production - Hammad Ali, Abu Mohammad; Isa, Siti Suriawati; Isa, Siti Salwa (Institute of Electrical and Electronics Engineers ( IEEE ), 2017)
The creative industries (CI) have become a global idea in the past few years. However, compared to developed countries such as Germany, the US, and the UK developing countries are far behind. Many developing countries in Asia region such as China, Indonesia, and Malaysia followed the CI model from the developed countries with some local contents added to it. Due to the novelty of this topic in most developing countries, data is not readily available in the literature. Thus, this study decided to close the significant gap in the literature by doing a research on the development of CI in Malaysia. At the end of the 20th century the Malaysian government initiated a large scale project to develop the Multimedia Super Corridor (MSC). This MSC project is part of Malaysia's preparation to become a developed country by the year 2020. With the global phenomenon on technology and multimedia for the last decade, Malaysia does not want to be left behind in this transformation. Hence, the government and the private sector have been working closely to develop the creative content industries, and to make the public aware of the importance of this ‘creative’ economy. Since, the concept of CI in Malaysia is still not clear, a case study method is identified as the best method to understand this sector in the country. This study approached Les'Copaque Production (LCP) an animated and 3D movie private company, to examine their experience in developing their CI products and services in Malaysia. Using a case study approach, a better knowledge and comprehension about the development of CI from Malaysia context would be gathered. This paper discusses the findings as well as some of the limitations of the methodology.